Analisis Persepsi Hakim Terhadap Pembayaran Uang ‘Iwad dan Khulu’ dalam Perceraian (Studi Kasus di Pengadilan Agama Wonosobo) - Afifah, Hasna (Qanun: Jurnal Hukum Keluarga Islam, 2023)
The background of this research is in terms of the ignorance of people about what the payment of ‘iwadh and khulu’ are in which they, in fact, have been stated in the sighot taklik talak as well as in the marriage certificate as issued by Ministry of Religion. Khulu’ is a divorce where a wife pays the amount of money as ‘iwadh (substitute) to the husband; meanwhile, ‘Iwadh refers to the pillar that is a must in doing the khulu’. In the hadith regulating about khulu’, it is stated that iwadh is given to the husband but in reality in the Religion Court it is not a must to be given. This is a field research using the qualitative method through interview and using the empirical juridical approach to obtain the information related. Meanwhile, the data were taken from the Religion Court of Wonosobo, and other data related to the payment of ‘iwadh and khulu’. This research is more focused on the issue of legal basis of verdict in the payment of ‘iwadh in Religion Court of Wonosobo. The basis of judge in determine the payment of ‘iwadh and khulu’ in a divorce in based upon the regulation of sighot taklik stated in the marriage certificate issued by the Religion Court. Meanwhile, in khulu’ the verdict is given by court when all subtitutes have been paid. Based upon this problem, the research focus is how the analysis on the payment of ‘iwadh and khulu’ in a divorce and what is the legal basis of the verdict about the payment of ‘iwadh and khulu’ in Religion Court of Wonosobo.